Strategi Promosi Media Sosial Pada Restoran Jepang Sakura SP - Agustina Fitrianingrum; Fadilla Dwi Aruny (Social Engagement: Jurnal Pengabdian Kepada Masyarakat, 2023)
The COVID-19 pandemic has driven the growth of digital marketing applications as a marketing tool in various aspects of the industry and at scale, including in the SME-sized restaurant industry. One of the promotional activities that are currently viral that affect consumer purchasing decisions is through the TikTok platform. The TikTok application is the latest viral platform that is an effective means of business promotion in Indonesia. Therefore, the involvement of TikTok as a social media platform has become an important promotion tool for Sakura SP restaurants. It helps Sakura SP restaurant to find customers. Creating a giveaway strategy increase the followers of its TikTok account. Some videos uploaded via Youtube is helpful to exist on social media. This activity encourages MSMEs to develop promotional strategies for the latest trends through digital platforms for the culinary business by using TikTok and Youtube on Sakura SP. This activity has helped Sakura SP to be more effective in promoting via many social media, especially TikTok.